PARTISIPASI MASYARAKAT DALAM PEMBINAAN DAN PENYULUHAN SISTEM KEAMANAN LINGKUNGAN DI KELURAHAN RAPPANG KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Yulianti T; Hariyanti Hamid; Saifullah Saifullah (JIA: Jurnal Ilmiah Administrasi, 2022)
This study aims to determine community participation in the development and extension of the Environmental Security System in Rappang Village, Panca Rijang District, Sidenreng Rappang Regency. The population in this study was 585, while the research sample was 59 people, this study used a quantitative descriptive method. Literature study, observation, and questionnaire techniques, data analysis techniques used are descriptive statistics, data quality test, classical assumption test using SPPS 21.0 and Likert scale. The results of this study indicate that the Community Participation Indicator with a value of 56.8% is categorized as “poor”, community participation with a value of 51.2% is categorized as “not good, and factors that affect discipline with a value of 70% are categorized as “good”.